Femtosecond laser structuring of novel electrodes for 3D fuel cell design with increased reaction surface. Issue 1777 (2015) - Faubert, Patrick; Müller, Claas; Reinecke, Holger; Smyrek, Peter; Proell, Johannes; Pfleging, Wilhelm
ABSTRACT: The scalable storage of renewable energy by means of converting water to hydrogen fuels electrochemically hinges on fundamental improvements in catalytic materials. However, many applications exist where an extended lifetime is virtually crucial for their functionality and success, e.g. in case of limited accessibility such as tire pressure sensors or biomedical implants. For these kinds of applications, the ultimate power supply should be a self-renewing energy source. This strategy is pursued by the concept of Micro Energy Harvesting (MEH). Within a MEH system a micro generator converts ambient energy to electrical energy for driving an application. Unfortunately, it is not ensured that the ambient energy level will maintain always high enough to provide sufficient power to the system as harvested energy usually manifests itself in rather irregular, random and low-energy bursts. One appealing form of integrated energy storage is the use of H2/air, a so called fuel cell type (FC) battery. Such devices promise very high volumetric energy densities of more than 2000 Wh/l. Consequently, this type of battery has recently attracted more and more attention and primary as well as secondary cells have been realized. Alkaline polymer electrolyte fuel cells have been recognized as the most promising solution in order to overcome the dependency on noble metal catalysts. Nevertheless, further improvements for these kinds of fuel cells have to be reached with respect to high power. Therefore, one promising approach is to increase the skin surface of porous chromium decorated nickel electrodes for enhancement of exchange current density by forming three-dimensional (3D) microstructures directly into the electrode. Therefore, a novel laser structuring process was applied using ultrashort laser pulses. Ultrashort laser processing of complex multimaterial systems for energy storage allow for precise material removal without changing the material properties. By applying this novel laser-based structuring technique, 3D microstructures could be formed permitting shortened diffusion lengths between the electrolyte and the electrode surface being necessary for increased exchange current densities.